Students’ perception on rapport in english classroom - Nova, Muhamad (Journal of Language and Applied Linguistics, 2020)
Rapport is necessary to establish effective teaching and learning process. To maintain the rapport, the EFL teachers need to find appropriate activities to be conducted in the classroom. Therefore, this study is established to investigate the EFL teacher’s activities in maintaining rapport in EFL classroom. By conducting a questionnaire survey to 125 students, the activities conducted by EFL teachers in maintaining rapport are identified. It reveals that the teacher has conducted 19 activities from 20 activities provided in maintaining rapport in EFL classroom based on students’ perception. EFL Teacher has not done showing their interest on students completely. EFL teacher needs to emphasize more their interest to students and try to approach them individually through group discussion. Furthermore, EFL teachers can evaluate their teaching activities to foster a positive learning environment. Further research is recommended to investigate the activities done by EFL teachers in maintaining rapport based on the teacher’s perception.